PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) MATERI HADAST DAN NAJIS DI KELAS VII B SMPS IT SULTHONIYAH SAMBASTAHUN PELAJARAN 2023/2024 - Sri Rahayu; Aslan Aslan; Eliyah Eliyah (CV. ADIBA AISHA AMIRA, 2025)
The purpose of this study is to investigate: 1) Student learning outcomes on the topic of hadast and najis in class VII B at SMPS IT Sulthoniyah Sambas before implementing the Make a Match learning model during the 2023/2024 academic year; 2) Student learning outcomes on the same topic in class VII B at SMPS IT Sulthoniyah Sambas after applying the Make a Match learning model during the 2023/2024 academic year; and 3) The impact of the Make a Match learning model on student learning outcomes in class VII B on the topic of hadast and najis at SMPS IT Sulthoniyah in the 2023/2024 academic year. This research employs a quantitative approach with a comparative research type in the form of a quasi-experiment. The population of the experiment consisted of 50 students, selected through purposive sampling. Data collection techniques included observation, tests, and documentation. The data analysis techniques applied were validity tests, reliability tests, normality tests, homogeneity tests, independent samples tests, and paired samples tests. The findings of the research are as follows: 1) The pre-test results from the Independent Samples Test, conducted before treatment, indicated a mean score of 66.09 for the experimental class and 65.14 for the control class, showing that the students’ abilities were similar before treatment. The Sig. (2-tailed) value was 0.753 > 0.05, indicating that Ho was accepted, and Ha was rejected, meaning there was no significant effect of the Make a Match learning model on student learning outcomes before treatment. 2) The post-test results from the Independent Samples Test, conducted after treatment, showed a mean student learning outcome of 76.19 in the experimental class and 69.33 in the control class, indicating that the experimental class had a higher average following treatment. The Sig. (2-tailed) value was 0.039 < 0.05, 3) The research design test value was 5.91, and the Paired Samples Test showed a Sig. (2-tailed) value of 0.000 < 0.05, meaning Ho was rejected, and Ha was accepted, indicating a significant effect of the Make a Match learning model on student learning outcomes for the topic of hadast and najis in class VII B at SMPS IT Sulthoniyah Sambas.